2021
DOI: 10.1177/1475921720986156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propagation distance on acoustic emission of carbon fiber/epoxy composites

Abstract: This study examined the change in acoustic emission as a function of measurement position of fiber-reinforced composites. Single-edge-notched carbon fiber/epoxy composites were prepared and tested under cyclic loading, with sensors located at specific distances from the end of the notch. Although the I b-value increased overall, the degree of increase significantly varied with position and acoustic emission frequency. Notably, the proportion of acoustic emission signals for each failure mode varied due to a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The b-value analysis tracks the amplitude trend of AE signals, showing a lower value at a severe damage state. To the authors' knowledge, the application of b-value analysis in composite materials is rare, and is a first in our research group [28][29][30][31]. In previous studies in our group, we revealed a specific frequency AE signal range for each fracture mode, and the b-value analysis is feasible in composite materials.…”
Section: Introductionmentioning
confidence: 79%
“…The b-value analysis tracks the amplitude trend of AE signals, showing a lower value at a severe damage state. To the authors' knowledge, the application of b-value analysis in composite materials is rare, and is a first in our research group [28][29][30][31]. In previous studies in our group, we revealed a specific frequency AE signal range for each fracture mode, and the b-value analysis is feasible in composite materials.…”
Section: Introductionmentioning
confidence: 79%
“…The AE signal is more susceptible to variations in the AE signal during long-distance propagation as the AE signal is normally attenuated by the material itself. 42 , 43 However, because wood belongs to anisotropic material, the kinetic energy change rules of the 3 sensors far away were inconsistent. To clearly explain this change, as shown in Figure 5 , slice dyeing was performed on the used Zelkova schneideriana specimen, and the internal structure of wood was observed by electron microscope.…”
Section: Resultsmentioning
confidence: 99%
“… 16 used the b-value to describe the statistical characteristics of signal amplitude, and then used the c-value and frequency fluctuations to characterize the frequency features of the signal, thereby analyzing the damage evolution process in GFRP composites. In other studies, 17 , 18 b-values and improved b-values (Ib-values, which are calculated based on the mean and standard deviation of the AE signal amplitude distribution) have been employed in AE damage evolution analysis for damage detection in composite materials. Wang et al.…”
Section: Introductionmentioning
confidence: 99%